Valorization of bamboo by γ-valerolactone/acid/water to produce digestible cellulose, degraded sugars and lignin. (April 2017) - Li, Shu-Xian; Li, Ming-Fei; Yu, Ping; Fan, Yong-Ming; Shou, Jia-Nan; Sun, Run-Cang
Graphical abstract: Highlights: Bamboo was valorized by γ-valerolactone/acid/water. Digestible cellulose, degraded sugars and lignin were obtained. Enzymatic hydrolysis was enhanced by 6.7-fold after treatment. The lignin obtained had high purity, low molecular weight and polydispersity. Abstract: A novel pretreatment process was developed to achieve valorization of bamboo components into digestible cellulose, degraded sugars and lignin. In this case, bamboo was pretreated with 60% γ-valerolactone (GVL)/40% water containing 0.05 mol/L H2 SO4, yielding solid fraction rich in cellulose. The resulting liquor was further treated with the addition of NaCl and ultrasound, resulting in water phase rich in degraded sugars and GVL phase containing lignin, which was easy to recover. Results showed that the enzymatic hydrolysis was enhanced by 6.7-fold after treatment as compared to the control. The degraded sugars released in water phase contained monosaccharides (70.72–160.47 g/kg) together with oligo- and polysaccharides (46.4–181.85 g/kg). The lignin obtained had high purity, low molecular weight (1820–2970 g mol −1 ) and low polydispersity (1.93–1.98). The present study creates a novel pretreatment process for the conversion of Gramineae biomass into useful feedstocks with potential applications in the fields of fuels, chemicals and polymers.